“FIRDAUS” DALAM KRITIK FEMINIS NAWAL EL SA’DAWI - Asrina Asrina (Kafa`ah: Journal of Gender Studies, 2011)
It was one too many of the lack of information concerning Islam and understanding textual doctrines of Islam,  used to spread out traditional believes considering gender bias.  Gender bias, which is represented in form of women subordination in communal interactions, is generally sparkled by common misperception on viewing women’s role in society, whether it is indigenous or merely derived from social construction. This misperception, of course, has placed men at superior position and crystallized as the culture of patriarchy. Moreover, this unfair patriarchal culture is often employed as approaches in interpreting religious texts that throw women away to the lower level in social status.In her explanation, by mentioning some social and culture of people who lived in Arabic areas, Nawal el Sa’adawi  indicated that gender equity is one of basic principles of al-Qur’an, the main source of religious texts for moslem community. But unfortunately,  that gender-related Qur’anic verses are often misinterpreted and misused. Therefore, she thought that reinterpretation of religious doctrine on women issues is exteremely fundamental. By linguistic literature points of view, Nawal el Sa’adawi tried to described and criticized the traditions of  moslem society in Arabic areas relating to gender bias.  Keywords : Bias Gender, Masyarakat Arab dan BudayaCopyright © 2011 by Kafa`ah All right reservedDOI: 10.15548/jk.v1i1.36